Analisis Karakteristik Gambar Anak dengan Lingkungan di SDN Ensa Kecamatan Mori Atas Sulawesi Tengah: Analysis of the Characteristics of Children's Drawings Depicting the Environment at SDN Ensa, Mori Atas District, Central Sulawesi - Astanti Sakaria; Andi Imrah Dewi; Kadek Hariana; Zulnuraini Zulnuraini; Hasna Hasanudin (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyse the characteristics of children's drawings and identify the connection between the surrounding environment and the visual representations produced by students at SDN Ensa, Mori Atas District, Central Sulawesi. The research employs a qualitative approach with a phenomenological study design. The research subjects—comprising students from grades IV, V, and VI, teachers, and parents—were selected using purposive sampling. Data were collected through participant observation, in-depth interviews, and documentation of the children's drawings. Data analysis involved data reduction, coding, visual analysis, theoretical interpretation, data presentation, and conclusion drawing. The results indicate a strong link between the children's drawings and their living environments. Among the 29 drawings analysed, the community environment was the most dominant theme (51.72%), followed by the family environment (20.69%), natural environment (17.24%), school environment (6.90%), and other themes (3.45%). Frequently depicted objects included houses, trees, rivers, mountains, roads, trucks, schools, and daily social activities. Colour usage was dominated by green, blue, brown, and yellow, reflecting actual environmental conditions. Furthermore, the children's visual capabilities demonstrated development corresponding to their grade levels, characterised by increased detail, composition, and spatial relationships within the drawings. Family, school, community, and natural environments were found to influence the characteristics of the drawings, with the community environment being the most dominant factor. These findings suggest that children's drawings reflect visual, social, emotional, and cultural experiences shaped by their interactions with their surroundings.